الوسائل الحديثة وأثرها في إرث الحمل - العبيد، أحمد بن سليمان بن صالح (عبد الفتاح محمود ادريس, 2018)
Allaah has made all those who associate him with the deceased one of the causes of inheritance. He has not left any male or female, small or large, even the fetus in the womb of his mother. He did not deny this right in the law of Allaah. The value of the inheritance is not divided between the heirs and the inheritance. The right of pregnancy is lost, or the primary division is divided and the final division is left to the postpartum, all in order to preserve the right of the fetus in the womb of his mother.
جعل الله تعالى لكل من يربطه بالمتوفى سبب من أسباب الإرث حق فيما تركه، ولم يستثن من ذلك ذكر أو أنثى، صغيرا أو كبيرا، حتى الجنين في رحم أمه، لم يحرم من هذا الحق في شرع الله تعالى، وذلك لتحقيق مقصد ضروري من مقاصد الشريعة الإسلامية، وهو حفظ المال على تقدير كونه وارثاً فلا تقسم التركة عند موت المورث بين الورثة، فيضيع حق الحمل، أو تقسم قسمة أولية ثم يترك التقسيم النهائي إلى ما بعد الولادة، كل هذا حفاظاً على حق الجنين في رحم أمه.
Keywords: الحمل والولادة -- المواريث -- الإرث -- الأجهزة الطبية الحديثة